Construction and Maintenance of the Optimal Photosynthetic Systems of the Leaf, Herbaceous Plant and Tree: an Eco-developmental Treatise - TERASHIMA, ICHIRO (Ann Bot, 2004)
• Background and Aims The paper by Monsi and Saeki in 1953 (Japanese Journal of Botany 14: 22–52) was pioneering not only in mathematical modelling of canopy photosynthesis but also in eco-developmental studies of seasonal changes in leaf canopies. • Scope Construction and maintenance mechanisms of efficient photosynthetic systems at three different scaling levels—single leaves, herbaceous plants and trees—are reviewed mainly based on the nitrogen optimization theory. First, the nitrogen optimization theory with respect to the canopy and the single leaf is briefly introduced. Secondly, significance of leaf thickness in CO(2) diffusion in the leaf and in leaf photosynthesis is discussed. Thirdly, mechanisms of adjustment of photosynthetic properties of the leaf within the herbaceous plant individual throughout its life are discussed. In particular, roles of sugar sensing, redox control and of cytokinin are highlighted. Finally, the development of a tree is considered. • Conclusions Various mechanisms contribute to construction and maintenance of efficient photosynthetic systems. Molecular backgrounds of these ecologically important mechanisms should be clarified. The construction mechanisms of the tree cannot be explained solely by the nitrogen optimization theory. It is proposed that the pipe model theory in its differential form could be a potential tool in future studies in this research area.